Arctic deep-water anoxia and its potential role for ocean carbon sink during glacial periods - Kwangchul Jang; Kyung Sik Woo; Jin-Kyoung Kim; Seung-Il Nam (Communications Earth & Environment, 2023)
Freshening and oxygen depletion of the polar deep waters of the Amerasian Basin during the last glacial periods probably resulted in significant carbon burial, according to geochemical analyses of inorganic authigenic carbonates in Arctic Ocean sediments.